Toward advanced modular drug and gene delivery system - Saeed, Aram Omer (2010)
In chapter two, the development of new a nanoparticulate carrier system for gene delivery was described. The new nanocarrier consists of a blend matrix formed by a poly (lactic-eo-glycolic acid) (PLGA) and Poly(ethylene glycol) bis (3-aminopropyl) terminated (also known as JeffamineTM). Nanopartic1es were formulated based on a 50:50 weight ratio of PLGA:Jeffamine using a modified emulsification-solvent diffusion technique. The potential of these blended matrix nanoparticles for encapsulation efficiency of Calf Thymus DNA and release profile were also studied. The achieved encapsulation efficiency of Calf Thymus DNA was approximately 84% for 0.4% theoretical loading with regard to total amount of PLGA. The PLGA: Jeffamine blended nanoparticles provided continuous and controlled release of Calf Thymus DNA. The PLGA:Jeffamine nanopartic1es were also coated with PLGA-PEGMA&75and PDMAEMA-PEGMA block copolymers using a simple physical adsorption method. After surface coating of the nanoparticles, zeta potential value showed significant reduction of surface charges from -38 mV to near zero value, while TEM micrographs showed a well defined core-shell nanoparticle. In chapter three, A facile route to biocompatible poly (lactic acid-coglycolic acid)-co-poly (ethyleneglycol methacrylate) (PLGA-PEGMA) block co-polymers was described utilising a combination of ring-opening polymerisation (ROP) and Radical Addition Fragmentation Transfer (RAFT) methods. A series of PLGA-PEGMA polymers varying in comonomer content and block length were synthesised with low polydispersities. All the block co-polymers formed micelles in aqueous solution as shown by dynamic light scattering, while critical micelle concentrations were found to be in the micromolar range. The polymer micelles were able to encapsulate model drugs(carboxyfluorescein and fluorescein isothiocyanate) and selected copolymer micelles incubated with 3T3 fibroblasts as a model cell line were rapidly taken up as indicated by fluorescence microscopy assays. The combination of the polymer chemistries opens the way to highly flexible syntheses of micellar drug carrier systems. In chapter four, multifunctional and modular block co-polymers prepared from biocompatible monomers and linked by a bioreducible disulphide linkage have been prepared using a combination of ring-opening and atom-transfer radical polymerizations (ATRP). The presence of terminal functionality via ATRP allowed cell-targeting folic acid groups to be attached in a controllable manner, while the block co-polymer architecture enabled well-defined nanopartic1es to be prepared by a water-oil-water double emulsion procedure to encapsulate DNA with high efficiency. Gene delivery assays in a Calu-3 cell line indicated specific folatereceptor-mediated uptake of the nanoparticles, and triggered release of the DNA payload via cleavage of the disulfide link resulted in enhanced transgene expression compared to non-bioreducible analogues. These materials offer a promising and generic means to deliver a wide variety of therapeutic payloads to cells in a selective and tuneable way.